Pre-operative prognostic nutrition index and post-operative pneumonia in aneurysmal subarachnoid hemorrhage patients - Xu, Manman; Zhang, Liang; Wang, Juan; Cheng, Longyang; Chen, Chunlei; Li, Shaoya; Dai, Haibin; Zhao, Penglai; Hang, Chunhua (Frontiers in Neurology, 2023)
Background and Objective: Post-operative pneumonia (POP), a common complication, may be associated with the prolonged hospitalization and long-term mortality in aneurysmal subarachnoid hemorrhage (aSAH) patients. This study aimed to explore the association between pre-operative prognostic nutrition index (PNI) and POP in aSAH patients. Methods: A total of 280 aSAH patients were enrolled from Nanjing Drum Tower Hospital. PNI were calculated as [10 × albumin(gr/dl)] + [0.005 × absolute preoperative lymphocyte count (per mm3)]. We utilized multivariate analyses, restricted cubic spline, net reclassification improvement (NRI), integrated discrimination improvement (IDI) to elucidate the role of PNI in POP. Results: Pre-operative PNI levels in the POP group were higher, compared with non-POP group (41.0 [39.0, 45.4] versus 44.4 [40.5, 47.3], P=0.001). When we included PNI as a categorical variable into the multivariate analysis, the levels of PNI were associated with POP (odds ratio, 0.433; 95% confidence interval, 0.253-0.743; P=0.002). In addition, when we included PNI as a continuous variable into the multivariate analysis, the PNI levels were also associated with POP (odds ratio, 0.942; 95% confidence interval, 0.892-0.994；P=0.028). Multivariable-adjusted spline regression indicated a linear dose-response association between PNI and POP in aSAH participants (P for linearity= 0.027; P for non-linearity= 0.130). Reclassification assessed by IDI and NRI was significantly improved with the addition of PNI to the conventional model of POP in aSAH patients (NRI: 0.322 [0.089 - 0.555], P=0.007; IDI: 0.016 [0.001 - 0.031], P= 0.040). Conclusion: The lower levels of pre-operative PNI may be associated with the higher incidence of POP in aSAH patients. Neurosurgeons are supposed to pay more attention to pre-operative nutrition status in aSAH patients. Keywords: prognostic nutrition index, aneurysmal subarachnoid hemorrhage, post-operative pneumonia, restricted cubic spline, net reclassification improvement, integrated discrimination improvement.